FREQUENCY OF METABOLIC SYNDROME IN PREMENOPAUSAL AND POSTMENOPAUSAL BREAST CARCINOMA PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the frequency of metabolic syndrome (MetS) in premenopausal and postmenopausal breast cancer females presenting at a tertiary care hospital.Design: Cross-sectional studyPlace & Duration of Study: Study was carried out at surgical unit 3 of Civil Hospital at Karachi, Pakistan from December 2024 to May 2025.Methodology: Female patients of age 35 to 70 years diagnosed with breast cancer were included. Based on menstrual history females were classified as premenopausal or postmenopausal. The International Diabetes Federation (IDF 2005) criteria was used to diagnose MetS, which require central obesity plus 2 or more of the following parameters: elevated triglycerides, elevated fasting glucose, low HDL cholesterol, or elevated blood pressure. Data regarding demographic, clinical, and biochemical characteristics were collected. SPSS version 23 was used. Descriptive statistics were estimated and stratified analysis was performed using Chi-square/Fisher’s exact tests.Results: Among 116 females, 96 (82.8%) fulfilled the criteria for MetS. Central obesity was present in 97(83.6%), low HDL in 116(100%), elevated BP in 100(86.2%), high triglycerides in 74(63.8%), and elevated fasting glucose in 78(67.2%). MetS was slightly more prevalent in postmenopausal 60(85.7%) compared to premenopausal women 36(78.3%), however the relationship showed no significant association (p=0.299). Age, marital status, income and residence were not associated with MetS.Conclusion: A high burden of metabolic syndrome was observed among newly diagnosed breast cancer patients, irrespective of menopausal status. These findings highlight the requirement for integrated metabolic screening and risk reduction approaches in breast cancer care.”